Status dan Keanekaragaman Fungi Mikoriza Arbuskula (FMA) pada Lahan Produktif dan Lahan Non Produktif - Zulfredi Zulfredi; Deni Elfiati; Delvian Delvian (Peronema Forestry Science Journal, 2015)
Existence and status of the AMF is influenced by biotic and abiotic factors. This research aims to study and know the status and existence of Arbuscule Mycorrhizal Fungi (AMF) on the land productive and non productive land. Soil samples derived from the productive and non productive land in Tanjung Anom. This research uses the filter to get the spores and staining method to determine root colonization. Results showed that AMF colonization in productive land obtained 17.83% with an average density of 80 spores / 50g soil, and the percent of AMF colonization in non productive land obtained 42.76% with an average density of 89 spores / 50g  soil. AMF spore types Glomus and Acaulospora on productive land obtained 13 spore types Glomus sp, and on non productive land obtained 14 spore types Glomus sp and 2 Acaulospora spore types. Total spore types were obtained 27 spore types, 25 types of spores Glomus sp and 2 Acaulospora sp spore types.Keywords : Productive Land, Non Productive Land, AMF, Spore, Colonization.